Social Presence, Teacher Guidance, and Instructional Clarity in Blended EFL Learning: Students’ Perceptions from an Indonesian Secondary School - Muhammad Fadli; Nurneni Sulfia Kaharuddin; Muhammad Fauzan (Published by Institut Teknologi Pendidikan Indonesia, 2026)
Blended learning has become a common approach in English as a Foreign Language (EFL) instruction in secondary schools in Indonesia and across Southeast Asia, reflecting a shift from exclusively face-to-face teaching to digitally mediated instruction. Despite its potential to enhance flexibility, resource accessibility, and learning continuity, students’ experiences with blended learning remain uneven, particularly in public senior high schools with differing levels of infrastructure and digital readiness. This study aims to examine students’ perceptions of blended learning in EFL instruction at SMAN 3 Maros, focusing on perceived benefits, challenges, and the balance between online and offline components. Using a descriptive research design, data were collected from twelfth-grade students through questionnaires and interviews. The findings show that students generally appreciate the flexibility and access to learning materials provided by blended learning, but face challenges related to internet connectivity, digital literacy, and limited interaction during online sessions. These results indicate that the effectiveness of blended EFL learning depends not only on instructional mode but also on implementation quality and institutional support.